Effect of fiber post space irrigation with different peracetic acid formulations on the bond strength and penetration into the dentinal tubules of self-etching resin cement - Belizário, Lauriê Garcia [UNESP]; Kuga, Milton Carlos [UNESP]; Hungaro Duarte, Marco Antônio; Só, Marcus Vinicius Reis; Keine, Kátia Cristina [UNESP]; Pereira, Jefferson Ricardo (Elsevier, 2019)
Statement of problem: The post space must be irrigated with solutions that do not interfere with the bond strength and enhance penetration into the dentinal tubules of self-etching resin cement. Which solution is best is unclear. Peracetic acid with different formulations appears to be a good option. Purpose: The purpose of this in vitro study was to evaluate the effect of irrigating the fiber post space by using 1% peracetic acid (PA) at low (LH) or high (HH) hydrogen peroxide concentration on the bond strength and penetration into the dentinal tubules of RelyX U200 self-etching resin cement. Material and methods: After intraroot preparation for fiber posts in 60 endodontically treated teeth, the specimens were divided into 4 groups (n=15) according to the irrigation protocol: CG (control), distilled water; NA (NaOCl), 2.5% sodium hypochlorite; LHPA, PA with a low concentration of hydrogen peroxide; and HHPA, PA with a high concentration of hydrogen peroxide. The fiber posts were then cemented with self-etching resin cement labeled with rhodamine. Cross sections of the thirds were obtained by confocal scanning microscopy and submitted to the push-out and cement penetration tests. The data obtained in the push-out tests were evaluated by using ANOVA and the Tukey post hoc test, and those data obtained in the confocal screening were evaluated by using the Kruskal-Wallis and Dunn (Bonferroni correction) tests (α=.05). Results: Bond strength values in the cervical third of the CG were higher than those in NA (P=.035) but similar to those of the other groups (P=.05). In the other thirds, CG and LHPA values were similar to one another (P=.05) but higher than those of NA and HHPA (P<.001). The penetration rate assessed by confocal scanning microscopy revealed similar results in the cervical third for all groups (P=.075), except for NA which provided the lowest penetration. In the remaining thirds, CG and LHPA provided the highest penetration rate (P=.015). Conclusions: The LHPA group had no negative effects on the bond strength and penetration into the dentinal tubules of the self-etching resin cement.